2021
DOI: 10.1038/s41467-021-21479-8
|View full text |Cite
|
Sign up to set email alerts
|

Calculating metalation in cells reveals CobW acquires CoII for vitamin B12 biosynthesis while related proteins prefer ZnII

Abstract: Protein metal-occupancy (metalation) in vivo has been elusive. To address this challenge, the available free energies of metals have recently been determined from the responses of metal sensors. Here, we use these free energy values to develop a metalation-calculator which accounts for inter-metal competition and changing metal-availabilities inside cells. We use the calculator to understand the function and mechanism of GTPase CobW, a predicted CoII-chaperone for vitamin B12. Upon binding nucleotide (GTP) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(126 citation statements)
references
References 68 publications
1
119
0
Order By: Relevance
“…This article presents an equilibrium thermodynamic framework for biological metalation which in turn will provide the context for understanding the magnitude of kinetic contributions. Notably, this approach alone largely explained metal specificity in the handful of systems examined to date and, in some cases, identified disparities that informed further experimentation into metal specificity, for example, into the contributions of adducts with nucleotide cofactors [ 7∗ , 8∗∗ , 9∗∗ ].…”
Section: Metals In Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article presents an equilibrium thermodynamic framework for biological metalation which in turn will provide the context for understanding the magnitude of kinetic contributions. Notably, this approach alone largely explained metal specificity in the handful of systems examined to date and, in some cases, identified disparities that informed further experimentation into metal specificity, for example, into the contributions of adducts with nucleotide cofactors [ 7∗ , 8∗∗ , 9∗∗ ].…”
Section: Metals In Proteinsmentioning
confidence: 99%
“…Differences in free energy for metal complex formation with Mg 2+ GTP-CobW versus the intracellular milieu (ΔΔ G ) in an ideal cell where sensors are at their midpoints identify favourable (red, also on panel b) or unfavourable (blue) thermodynamic gradients for metalation. A metalation calculator compares such values to calculate in vivo metal occupancies [ 9 ]. …”
Section: Associative Metalation and Available Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Escherichia coli strains, ED656 and ED662 (ΔbtuF), were also used as B 12 -producers. E. coli strain ED656 was constructed in a similar fashion to ED741 (Young et al ., 2021). ED656 was generated from E. coli MG1655 by engineering it to contain a set of B 12 biosynthesis genes.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20] Furthermore, zinc ions are not homogeneously distributed within the cells, with large differences among cellular compartments and organelles. 21,22 Zinc has a key role in the signalling pathways of the innate and adaptive immune reactions. 23,24 It has been reported that zinc is able to participate in many processes of defense against infections.…”
mentioning
confidence: 99%